Juozas Tumas-Vaižgantas in the University - Vaitiekonienė, Aldona (Literatūra, 1970)
Juozas Tumas-Vaižgantas (1869-1933), a prominent Lithuanian writer, is known mainly for his prose work. But he was also inclined to do some literary research work. Lecturing at the University for almost ten years strengthened these inclinations and made it possible for J. Tumas to concentrate on a number of topical questions concerning the history of Lithuanian literature. His literary essays were in many cases based on lectures delivered before Humanities students at the Kaunas State University. The greater bulk of these lectures was published in separate edition or in vol. XI-XIV of the "Collected works by Vaižgantas". J. Tumas’s essays, concerning the Lithuanian literature of the past, are interesting works, marked by a vivid personal note and valuable for their abundance of fact. The most successful works in this field are devoted to such writers as Antanas Baranauskas, Vincas Kudirka, Maironis. While doing his research work J. Tumas was particularly interested in relations between literature and history and in the world of ideas, incorporated by works of art. Himself a writer, he usually shows a good insight into the artist’s psychology. A number of essays by J. Tumas express interesting historical, philosophical and aesthetic conceptions. J. Tumas preferred analytic methods in his literary research work, this was partly caused by the peculiarities of his object and material, the Lithuanian literature of the 19th century. The facts compiled by J. Tumas as well as his insight into the work of many 19th-century Lithuanian writers have proved useful to contemporary literary research work in Soviet Lithuania.